2018
DOI: 10.1021/acs.jpcc.8b03627
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Hydrogen Adsorption on Graphene by Gate Voltage

Abstract: In order to realize applications of hydrogen-adsorbed graphene, a main issue is how to control hydrogen adsorption/desorption at room temperature. In this study, we demonstrate the possibility to tune hydrogen adsorption on graphene by applying a gate voltage. The influence of the gate voltage on graphene and its hydrogen adsorption properties was investigated by electrical transport measurements, scanning tunneling microscopy, and density functional theory calculations. We show that more hydrogen adsorbs on g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…Graphene metamaterials exhibit many exotic physical phenomena because of its electrons in graphene behaving like massless Dirac fermions . Fermi energy of graphene can be effectively regulated by adjusting the electric field. , To make a thorough study on the tunable PIT effect, the transmission spectra with different E F are explored elaborately in Figure . It can be clearly observed that the PIT window demonstrates a distinct blue shift as the E F varies from 0.9 to 1.2 eV, namely, the transparency window moves into the higher frequency region with a larger E F .…”
Section: Resultsmentioning
confidence: 99%
“…Graphene metamaterials exhibit many exotic physical phenomena because of its electrons in graphene behaving like massless Dirac fermions . Fermi energy of graphene can be effectively regulated by adjusting the electric field. , To make a thorough study on the tunable PIT effect, the transmission spectra with different E F are explored elaborately in Figure . It can be clearly observed that the PIT window demonstrates a distinct blue shift as the E F varies from 0.9 to 1.2 eV, namely, the transparency window moves into the higher frequency region with a larger E F .…”
Section: Resultsmentioning
confidence: 99%
“…Although particularly interesting in view of the high thermal conductivity and carrier mobility, graphene suffers from the lack of an electronic band gap, achieved only through breaking of crystal symmetry, e.g. via hydrogenation or application of an electric field . Research on graphene triggered the discovery of new 2D materials, and, among them, exfoliated bP seems to be particularly appealing in view of its band gap, the value of which depends on the number of stacked layers.…”
Section: Introductionmentioning
confidence: 99%
“…via hydrogenation or application of an electric field. [13] Research on graphene triggered the discovery of new 2D materials, and, among them, exfoliated bP seems to be particularly appealing in view of its bandgap, the value of which depends on the number of stacked layers. In this regard, the direct bandgap may be tuned from 0.3 eV for bulk bP up to ca.…”
Section: Introductionmentioning
confidence: 99%
“…Для того чтобы создать щель, нужно нарушить условия идеальности [4,5]. Одним из способов является адсорбция чужеродных атомов [6][7][8]. Подавляющее число теоретических работ по адсорбции на графене выполнено в рамках DFT (density functional theory) [6][7][8][9][10].…”
unclassified
“…Одним из способов является адсорбция чужеродных атомов [6][7][8]. Подавляющее число теоретических работ по адсорбции на графене выполнено в рамках DFT (density functional theory) [6][7][8][9][10]. Здесь мы рассмотрим взаимодействующие между собой адчастицы при различных их концентрациях, воспользовавшись для этого методом функций Грина [11,12].…”
unclassified